Epistemology of Islamic Morality: Analyzing the Sedulang Setudung Tradition through Ibn Miskawaih’s Perspective - Ahmad Ihwani; Abdullah Idi; Nuraida Nuraida; Duski Ibrahim; Hamidah Hamidah (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2026)
This study explores the relationship between local traditions and societal morality within the context of ethics and Islamic thought. With concerns about moral decline and weakening community bonds amid modernization and individualistic digital culture in Indonesia, there is an urgent need to strengthen ethical foundations rooted in local wisdom to maintain social cohesion. A noticeable effect of this decline is the reduction in participation in tradition-based social activities in South Sumatra, which historically fostered the transmission of moral values. This research specifically analyzes the Sedulang Setudung tradition in Banyuasin as a medium for character development and examines its epistemological foundations through Ibn Miskawaih’s thought. Using a qualitative approach, the study incorporates participatory observation, in-depth interviews, and documentation of traditional practices. The analysis reveals that the Sedulang Setudung tradition transmits values such as togetherness, social solidarity, and collective responsibility, internalized through cultural symbols and communal participation. According to Ibn Miskawaih, this process aligns with the concept of ta‘wīd al-nafs, where virtue is cultivated through repeated actions, becoming ingrained character traits. The findings underscore that local traditions serve not just as heritage but also as vital tools for moral education, enhancing the ethical resilience of society. This research contributes to Islamic moral philosophy by emphasizing the integration of local wisdom and Islamic ethics to strengthen contemporary societal morality.